Evaluation of Polyherbal Formulation at Different Dose Levels on Egg Production and Egg Quality Parameters in White Leghorn layers fed with High Energy Diets (Global Journal of Medical Research, 2022)
Choline is an essential nutrient in the poultry diet. It plays a vital role in the metabolism and mobilization of accumulated abdominal fat. In layer birds, it helps in improving the rate of egg production, egg quality and prevents fatty liver syndrome. However, synthetic choline has lots of demerits that need to be addressed. To mitigate the drawbacks of choline, the present study was conducted to evaluate the impact of Kolin Plus TM , a polyherbal formulation (POH) manufactured by M/s Natural Remedies Pvt Ltd, Bengaluru, India, on the performance of the White Leghorn (WL) layer poultry birds. In the current trial, WL layer hens at the age of 41 to 55 weeks were distributed into 7 (G1 to G7) study groups having 6 replicates (20 birds/replicate) per group. All groups (G2 to G7) except the normal control group (G1) were supplied with high energy diet (HED).
Keywords: layer poultry birds; choline chloride; polyherbal formulation; egg production